PENERAPAN SIMPLEQUEUE PADA BANDWIDTH MANAGEMENT MIKROTIK RB941 – 2ND UNTUK PEMBATASAN BANDWIDTH INTERNET - Pritiy Singgam; Thania Dealva Arsyad; Afifah Naila Nasution; Dedy Kiswanto (LPPM Universitas Dhyana Pura, 2026)
The rapid development of information technology demands a reliable and efficient internet network. One common issue in network usage is the uneven distribution of bandwidth, which results in some users enjoying smooth internet access while others face disruptions. This study aims to analyze and explain the implementation of the Simple Queue feature on the Mikrotik RB941–2nD device as a solution for bandwidth management. The method used is an applied experiment by configuring data rate limitations and setting packet priorities on a WiFi network. The purpose of this test is to evaluate the effectiveness of the Simple Queue feature on the MikroTik router in limiting internet bandwidth for each device on the network. The configuration sets a bandwidth limit of 64 kbps, tested through the Rate graph on the MikroTik interface and a speed test from the client side. The test results show that the client device receives a download speed of only 0.04 Mbps and an upload speed of 0.18 Mbps when the restriction is active, which is close to the predefined limit. This proves that the Simple Queue feature successfully performs its function in controlling bandwidth usage according to the specified schedule, namely Monday to Friday from 08:00 to 12:10. This limitation also effectively prevents internet access domination by a single device, allowing for more equitable connection distribution. However, the 64 kbps speed limit is considered too low for current internet activity needs and should be adjusted to continue supporting an optimal user experience.